Distributed command governor strategies for multi-agent dynamical systems - Francesco Tedesco, Francesco Tedesco; Palopoli, Luigi; Casavola, Alessandro (My University, 2011)
This dissertation presents a class of novel distributed supervision strategies for multi-agent linear systems connected via data networks and subject to coordination constraints. Such a coordination-by-constraint paradigm is characterized by a set of spatially distributed dynamic systems, connected via communication channels, with possibly dynamical coupling amongst them which need to be supervised and coordinated in order to accomplish their overall objective. The basic design philosophy of the Command Governor (CG) set-point management is used here in order to maintain a pre-stabilized system within prescribed constraints. While in traditional CG schemes the set-point manipulation is undertaken on the basis of the actual measure of the state, in this dissertation it is shown that the CG design problem can be solved also in the case that such an explicit measure is not available by forcing the state evolutions to stay ”not too far” from the manifold of feasible steady-states. This approach, referred to as Feed-Forward CG (FF-CG), is a convenient solution to be used in distributed applications where the cost of measuring the overall state and distributing it amongst the agents may be a severe limitation. Several distributed strategies, based both on CG and FF-CG ideas, will be fully described and analyzed. First, we propose some “non-iterative” schemes in which the agents acting as supervisors communicate once during the decision process. In this respect, a “sequential” distributed strategy in which only one agent at the time is allowed to manipulate its own reference signal is proposed. Such a strategy, although interesting by itself in some applications, will be instrumental to introduce a more effective “parallel” distributed strategy, in which all agents are allowed, under certain conditions, to modify their own reference signals simultaneously. Then an “iterative” procedure, borrowed from the literature, has been here adapted in order to build more efficient distributed schemes which however require larger amount of data exchanges for their implementation. With the aim of evaluating the distributed methods here proposed, several cases of study involving the coordination autonomous vehicles, power networks and water networks management are illustrated.
Dottorato di Ricerca in Ingegneria dei Sistemi e Informatica XXIV Ciclo, a.a. 2011
Keywords: Automazione; Algoritmi